Formulation of Strategies to Minimize Dropshipping Business Failure on Shopee Indonesia through the Business Model Canvas, SWOT Analysis, and TOWS Matrix - Fani Al Vionita Rangkuti; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (Pusat Riset dan Inovasi Nasional, 2026)
The rapid growth of e-commerce in Indonesia has increased business actors’ interest in the dropshipping business model, particularly on the Shopee platform. Although this model offers operational convenience and relatively low capital requirements, the failure rate of dropshipping businesses remains high due to dependence on suppliers and affiliates, fluctuations in promotional costs, and the dynamic nature of platform algorithms. This study aims to formulate strategies to minimize dropshipping business failure on Shopee Indonesia through the integration of the Business Model Canvas (BMC), SWOT analysis, and the TOWS Matrix. This research employs a descriptive qualitative approach, with data collected through in-depth interviews with active dropshipping practitioners on Shopee Indonesia. The data were analyzed by mapping the nine elements of the Business Model Canvas, identifying internal and external factors using SWOT analysis, and formulating strategic alternatives through the TOWS Matrix. The findings indicate that the existing dropshipping business model functionally fulfills all nine blocks of the Business Model Canvas; however, it still faces key weaknesses, including high dependence on external parties, substantial promotional cost burdens, and risks arising from changes in platform policies. The integration of SWOT and TOWS analyses generates SO, WO, ST, and WT strategies that emphasize service quality enhancement, optimization of digital marketing, utilization of automation technologies, supplier diversification, and more efficient cost management. This study concludes that the integration of the Business Model Canvas, SWOT analysis, and the TOWS Matrix represents an effective strategic approach to enhancing business stability, competitiveness, and sustainability within the Shopee Indonesia marketplace ecosystem